1991
DOI: 10.1002/jcc.540120113
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio characterization of several states of nitroxylium (NO). Comparison of fragmentation energies of nitroxylium, nitroxyl (NO3), and nitrate

Abstract: Ab initio calculations have been performed at the self-consistent field (HF') level, and its perturbative extensions up to fourth-order (MPn), for several electronic states of nitroxylium (NO;) as well as for a large number of reference species. Geometries are optimized at the HFiDZ and HF/DZP levels (double zeta and double zeta plus polarization bases). The ground state is found to be the D, 'A; state, with the C,,, 'A, (closed Y ) state higher by 0.94 eV. The relationship between adding electrons or oxygen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…Photo-oxidation of the parent 3,7-dimethylenebicyclo-[3.3.1]nonane (18) [31] and 3-ethylidene-7-methylenebicyclo- (19) in the presence of TCB gives the same products as found for the photo-oxidations of propellanes 3 and 4. Thus, oxidation must occur via the same radical cation intermediates (in curly brackets in Scheme 2).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Photo-oxidation of the parent 3,7-dimethylenebicyclo-[3.3.1]nonane (18) [31] and 3-ethylidene-7-methylenebicyclo- (19) in the presence of TCB gives the same products as found for the photo-oxidations of propellanes 3 and 4. Thus, oxidation must occur via the same radical cation intermediates (in curly brackets in Scheme 2).…”
Section: Resultssupporting
confidence: 53%
“…The electron affinity of NO 3 • , computed for the NO 3 • /NO 3 Ϫ couple is only 90.0 and 94.8 kcal/mol at B3LYP and CCSD(T)/cc-pVTZ, respectively, [18] (experimentally 90.4 kcal/mol), [19] and is too low to oxidize aromatic hydrocarbons [Equation (1)]. Similarly, the nitrosonium cation NO ϩ (electron affinity ϭ 224.2 kcal/mol [20] ) is known to be an effective SET oxidant only for some easily oxidizable aromatic compounds.…”
mentioning
confidence: 99%
“…(B) The energy derivative of the photoion efficiency spectrum on NO3 between 1 = 97.0 and 100.0 nm. The maximum in the derivative is at 1 = 98.675 nm (IE = 12.565 eV).HNO, -NO^+ + H(4) would be expected to occur at ionization energies close to 17 eV. This prediction was confirmed by observation of a weak signal for N03+ (from HN03) with an onset at ca.…”
mentioning
confidence: 51%
“…While experiments pointed to a D 3h symmetrical structure, 14 -20 most calculations favored a C 2v geometry. [21][22][23][24][25][26][27][28][29][30] In our recent work we showed that most of those theoretical results were flawed by the pronounced symmetry breaking of the electronic wave function, for which NO 3 is almost a textbook example. 31 The reason for symmetry breaking is that the zerothorder Hamiltonian Ĥ 0 , usually the N-electron Hartree-Fock ͑HF͒ operator, is a poor approximation of the physical system, and eigenfunctions are determined that violate the commutator relation ͓Ĥ 0 ,Ô ͔ϭ0 where Ô is the symmetry operator of the nuclear point group.…”
Section: Introductionmentioning
confidence: 99%
“…26 In a very recent study, Heryadi and Yeager calculated the photoelectron spectrum of NO 3 by a multireference Green's function method which in principle should be capable of handling the symmetry-breaking properties of this radical correctly. 36 In fact, they obtained ionization potentials in a͒ Electronic mail: wolfgang.eisfeld@ch.tum.de b͒ Electronic mail: morokuma@emory.edu close agreement with the experiment of Wang et al However, it unfortunately turns out that they used a CASSCF reference wave function which inevitably is symmetry broken.…”
Section: Introductionmentioning
confidence: 99%